Burnout Syndrome and its repercussions on nurses' daily work (Research, Society and Development, 2021)
Objective: To identify the main manifestations of Burnout Syndrome in Intensive Care Nurses. Methodology: This is a descriptive study carried out through the application of the Maslach Burnout Inventory (MBI). It was carried out in three adult intensive care units and one neonatal unit in a large philanthropic hospital. Eighteen nurses participated in the research, who carry out activities in the participating units. Results: The researched population was motivated and satisfied with the work, recognizing the importance of the work they do. Conclusion: The results obtained showed that, despite the work being considered strenuous and there are signs of exhaustion on the part of the professionals, there was not a great deal of professional exhaustion.